Retrotransposons and the brain: Exploring a complex relationship between mobile elements, stress, and neurological health - Amelia Cuarenta (Neurobiology of Stress)
Environmental experiences during early life, including stress, can significantly impact brain development and behavior. Early life stress (ELS) is linked to an increased risk for various psychiatric disorders including anxiety, depression, and substance use disorders. Epigenetic mechanisms have increasingly been of interest to understand how environmental factors contribute to reprogramming the brain and alter risk and resilience to developing psychiatric disorders. However, we know very little about mobile elements or the regulation of mobile elements and their contribution to psychiatric disorders. Recently, advances in genomics have contributed to our understanding of mobile elements, including the retrotransposon LINE-1 (L1) and their potential role in mediating environmental experiences. Yet we still do not understand how these elements may contribute to psychiatric disorders. Future research leveraging cutting-edge technologies will deepen our understanding of these mobile elements. By elucidating their role in development and how stress may impact them, we may unlock new avenues for therapeutic and diagnostic innovations.